J-TEXT achievements in turbulence and transport in support of future device/reactor - CHEN, Zhipeng; HUANG, Zhangsheng; JIANG, Min; LONG, Ting; WANG, Lu; GUO, Weixin; YANG, Zhoujun; LIU, Hai; LAN, Tao; ZHAO, Kaijun; XU, Yuhong; KE, Rui; et al. (Plasma science & technology, 2024)
Following the reconstruction of the TEXT tokamak at Huazhong University of Science and Technology in China, renamed as J-TEXT, a plethora of experimental and theoretical investigations has been conducted to elucidate the intricacies of turbulent transport within the tokamak configuration. These endeavors encompass not only the J-TEXT device’s experimental advancements but also delve into critical issues pertinent to the optimization of future fusion devices and reactors. The research includes topics on the suppression of turbulence, flow drive and damping, density limit, non-local transport, intrinsic toroidal flow, turbulence and flow with magnetic islands, turbulent transport in the stochastic layer, and turbulence and zonal flow with energetic particles or helium ash. Several important achievements have been made in the last few years, which will be further elaborated upon in this comprehensive review.